Prevalence and risk factors of metabolic syndrome in Ethiopia: describing an emerging outbreak in HIV clinics of the sub-Saharan Africa – a cross-sectional study - Helen Yifter; Ighovwerha Ofotokun; Wondwossen Amogne Degu; Abdurezak Ahmed Abdela; Ahmed Reja; Aster Shewaamare (BMJ Open)
Objectives HIV-induced chronic inflammation, immune activation and combination antiretroviral therapy (cART) are linked with adverse metabolic changes known to cause cardiovascular adversities. This study evaluates the prevalence of lipodystrophy, and metabolic syndrome (MetS), and analyses risk factors in HIV-infected Ethiopians taking cART.Methods A multicentre cross-sectional study was conducted at tertiary-level hospitals. Eligible participants attending the HIV clinics were enrolled. Sociodemographic, anthropometric, clinical, HIV treatment variables, lipid profile, fasting blood glucose level, risk factors and components of MetS, also lipodystrophy, were studied. Data were analysed by SPSS statistical package V.25 with descriptive and analytical statistics. For multivariable analysis of risk factors, a logistic regression model was used. Results were presented in frequency and percentages, mean±SD, or median+IQR. Statistical significance was taken as p<0.05.Results Among 518 studied participants, two-thirds were females, and the mean age of the study population was 45 years (SD=11). The mean duration of cART was 10 years (SD=4). Median CD4 count was 460 cells/mm3. The prevalence of MetS according to the Adult Treatment Panel III (2005) criteria was 37.6%. In multivariable analysis, independent risk factors for MetS were age >45 years (aHR 1.8, 95% CI 1.2 to 2.4), female sex (aHR 1.8, 95% CI 1.1 to 2.8), body mass index (BMI)>25 kg/m2 (aHR 2.7, 95% CI 1.8 to 4.1), efavirenz-based cART (aHR 2.8, 95% CI 1.6 to 4.8) and lopinavir/ritonavir-based cART (aHR 3.7, 95% CI 1.0 to 13.3). The prevalence of lipodystrophy was 23.6%. Prior exposure to a stavudine-containing regimen was independently associated with lipodystrophy (aHR 3.1, 95% CI 1.6 to 6.1).Conclusion Our study revealed 38% of the participants had MetS indicating considerable cardiovascular disease (CVD) risks. Independent risk factors for MetS were BMI≥25 kg/m2, efavirenz and lopinavir/ritonavir-based cART, female sex and age ≥45 years. In addition to prevention, CVD risk stratification and management will reduce morbidity and mortality in people with HIV infection.